AI for Effective use of Water in India for Crop Cultivation - Chinmay Rawat (International Journal of Intelligent Systems and Applications in Engineering, 2023)
India has the largest rain-fed agricultural land area and agro based economy in the world. This is due to the fact that 61% of agricultural families in India only utilise rainwater for their crops. The present study’s objective is to determine how artificial intelligence (AI) may be used to successfully utilise rainwater for agricultural production of ragi crop in India. Also, with aid of AI, the ideal day to plant a certain crop in order to maximise the use of rainfall, prevent ragi crop damage from untimely rain, and lower the total cost of agricultural production by using less irrigation water have been reported. The historical rainfall data for Bangalore area was collected from Metostat, weather future predictions were collected fromWeather.com, and Python was used for programming. To determine the entire cost of irrigation for the ragi crop, architects were hired. The calculation shows that if the ragi crop were sown on June 1 instead of May 23, 2022, we would have paid 30% less for water irrigation. To sum up, artificial intelligence may be utilised to forecast the ideal day to plant the ragi crop for the highest yield, while also lowering the overall cost of irrigation for agricultural production.